Luminescence tuning and exciton dynamics of Mn-doped CsPbCl3 nanocrystals. Issue 43 (25th October 2017) - De, Apurba; Mondal, Navendu; Samanta, Anunay
Abstract : In Mn-doped CsPbCl3 nanocrystals, Mn photoluminescence is widely tuned from yellow to red and exciton–dopant energy transfer timescales have been estimated through ultrafast transient absorption measurement. Abstract : Mn-Doped perovskite nanocrystals (NCs) are a new class of materials offering exciting opportunities to control over their optical and magnetic properties. Herein, we report a series of Mn-doped CsPbCl3 NCs exhibiting a tunable Mn photoluminescence (PL) band with a PL peak wavelength pushed up to 625 nm and tuned over a range of 40 nm, the largest achieved so far, by only varying the Mn content. The X-band EPR data and Mn PL decay behaviour of the NCs reveal that the exchange interaction between Mn 2+ ions is mainly responsible for a large shift of the Mn PL band. Ultrafast pump–probe measurements show that exciton–dopant energy transfer in these NCs is slower (∼50–100 ps) than trapping of the carriers (∼8–10 ps) in the host lattice. The large PL tuning reported here along with the insights into the mechanism of tuning and carrier dynamics are expected to boost the potential of Mn-doped CsPbCl3 NCs in light-powered devices.